If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + -3 = -15m Reorder the terms: -3 + 6m = -15m Solving -3 + 6m = -15m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '15m' to each side of the equation. -3 + 6m + 15m = -15m + 15m Combine like terms: 6m + 15m = 21m -3 + 21m = -15m + 15m Combine like terms: -15m + 15m = 0 -3 + 21m = 0 Add '3' to each side of the equation. -3 + 3 + 21m = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 21m = 0 + 3 21m = 0 + 3 Combine like terms: 0 + 3 = 3 21m = 3 Divide each side by '21'. m = 0.1428571429 Simplifying m = 0.1428571429
| 8x+24y=16 | | 0x+0y=15 | | 6m-3=15m | | -11-6a=1a-4 | | 3/5-8(8.8) | | 8y-26=-64+2y | | 2*x^3-3*x^2-36*x+5=0 | | 2z-28=8+8z | | .07*x=84 | | 5x-12=-17 | | 11/3*-7/2*4/5-x | | 3(a-1)=-17 | | 2*x^3-2*x^2-36*x+5=0 | | 0=121p^2-100 | | m*(-4/5)=2,23 | | 4(3x+4x)-1=91 | | .5z-1=-13 | | 7-2Inx=3 | | 800x-0.55=400x+0.45 | | f(x)=9x^2+4x+9 | | 2(j-4)=10 | | 2*16+46=x | | 2*16+46= | | x^2-cx-6c^2=0 | | 5x^10-8x^7= | | .66c+6=18 | | 3x/5-2 | | 20=y/6 | | 3^2/2n4=3 | | (1-2sinx)/cosx | | 2(5x-8)=7-(5-x) | | 1-2sinx/cosx |